Dismissal from employment and remedies, 2nd ed. - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2014)
The power to dismiss workers from employment is an extremely powerful economic sanction possessed by the employer. This deprives a worker of his livelihood resulting in financial loss and if unemployment is prolonged, it may involve the worker and his or her family in actual deprivation of the necessities of life. Therefore, any impending dismissal must be substantively justified and procedurally fair. The author of this book has examined issues relating to workers’ security of tenure, types and grounds of dismissal and its remedies including the mode of its enforcement. The author had discussed a full range of legislations and case laws on this area, both from Malaysia and from other jurisdictions.